Piezo-Assisted Turbinoplasty: A Novel Rapid and Safe Technique - Robotti, Enrico; Khazaal, Ali; Leone, Francesco (Facial Plastic Surgery, 2020)
Consensus is still lacking on the ideal treatment of turbinate hypertrophy concurrent with rhinoseptoplasty. A novel technique of turbinoplasty consisting of incision-bone fracturing by the use of piezoelectric technique—intramucosal microcauterization—lateralization is described in detail. A series of 157 consecutive patients is reviewed with a maximum follow-up of one year. The technique is fast and easy and allows predictability in avoiding postoperative bleeding and preventing remedialization of the lateralized turbinates. Due to the technology required, its use is suggested especially when piezo is employed during other steps of rhinoseptoplasty.
Keywords: turbinate hypertrophy; turbinates; turbinoplasty; nasal obstruction; piezoelectric